Change in the Gingival Margin Profile After the Single Flap Approach in Periodontal Intraosseous Defects. Issue 9 (1st September 2015) - Farina, Roberto; Simonelli, Anna; Minenna, Luigi; Rasperini, Giulio; Schincaglia, Gian Pietro; Tomasi, Cristiano; Trombelli, Leonardo
Abstract : Background: The aim of the present study is to evaluate the association of patient‐related and site‐specific factors, as well as the adopted treatment modality, with the change in buccal (bREC) and interdental (iREC) gingival recession observed at 6 months after treatment of periodontal intraosseous defects with the single flap approach (SFA). Methods: Sixty‐six patients contributing 74 intraosseous defects accessed with a buccal SFA and treated with different modalities were selected retrospectively. A two‐level (patient and site) model was constructed, with the 6‐month changes in bREC and iREC as the dependent variables. Results: 1) Significant 6‐month increases in bREC (−0.6 ± 0.7 mm) and iREC (−0.9 ± 1.1 mm) were observed. 2) bREC change was significantly predicted by presurgery interproximal probing depth (PD) and depth of osseous dehiscence at the buccal aspect. 3) iREC change was significantly predicted by presurgery interproximal PD and the treatment modality, with defects treated with SFA in combination with a graft material and a bioactive agent being less prone to iREC increase compared to defects treated with SFA alone. Conclusions: After buccal SFA, greater post‐surgery increase in bREC must be expected for deep intraosseous defects associated with a buccal dehiscence. The combination of a graft material and a bioactive agent in adjunct to the SFA may limit the postoperative increase in iREC.